1987
DOI: 10.1159/000118655
|View full text |Cite
|
Sign up to set email alerts
|

Architectonics of the Thalamus in the Echidna <i>(Tachyglossus aculeatus):</i>Search for the Mediodorsal Nucleus

Abstract: Architectural characteristics of the thalamus in echidnas and rats were compared in sections stained to reveal cell bodies, myelin, acetylcholinesterase, succinate dehydrogenase and cytochrome oxidase. Numerous species differences were noticed: in general, the thalamus is architecturally more homogeneous in echidnas than in rats, especially anteriorly. In this report we emphasize the presence of a relatively large structure localized in the anteromediodorsal part of the thalamus in echidnas. This structure, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
(37 reference statements)
2
13
0
Order By: Relevance
“…The thalamic nuclei of the echidna have been described in recent years by Welker and Lende [1980], Jones [19851 and, in part, by Ulinski [1984], In our own study [Regidor and Divac, 1987], additional observations about the thalamus in echidna can be found. In the present paper the posi tion of the labelled neurons in the thalamus is topo graphic, i.e., it does not refer to any existing labelling system.…”
Section: Histologysupporting
confidence: 66%
See 3 more Smart Citations
“…The thalamic nuclei of the echidna have been described in recent years by Welker and Lende [1980], Jones [19851 and, in part, by Ulinski [1984], In our own study [Regidor and Divac, 1987], additional observations about the thalamus in echidna can be found. In the present paper the posi tion of the labelled neurons in the thalamus is topo graphic, i.e., it does not refer to any existing labelling system.…”
Section: Histologysupporting
confidence: 66%
“…The results have shown that the large anteromediodorsal thalamic region, which in the present study contains la belled perikarya, is divisible into a medial, 'polymorphic' and a lateral, 'monomorphic' part. We have concluded that the an teromediodorsal region of the echidna thalamus consists mainly of tissue which may correspond to the MD in placentals [Regidor and Divac, 1987]. Unless the afferents of this thalamic nucleus in the echidna differ considerably from those of the MD in placental mammals, or unless the frontal cortex outside of the injected areas (e.g., the posterolateral edge and posterior parts of the ventral cortical sheet) receives other thalamic projections, our data may be taken as evidence that the cortex in front of sulcus beta in this species should be considered by definition to be the prefrontal area.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The similar organisation of spinal nuclear groups in Eutheria and this monotreme suggests that spinal cord cytoarchitecture was highly conserved throughout radiation of the mammals, in contrast to the unique organisational features of the diencephalon and cortex in monotremes [Lende, 1964;Regidor and Divac, 1987;Krubitzer et al. 1995].…”
Section: Echidna T1 Fasciculus Gracilismentioning
confidence: 98%